A social realist account of constraints and enablements navigated by South African students during the four year professional accounting programme at Rhodes University, South Africa - Myers, Lyndrianne Peta (Rhodes University, Faculty of Education, Department of Education, 2019)
This dissertation is an analysis of the enablements and constraints navigated by 43 students from different academic years within the Department of Accounting, Rhodes University, in their pursuit of obtaining the postgraduate Diploma in Accounting (DipAcc) qualification. Passing this diploma year entitles students to become Trainee Accountants, which is one of the requirements for their ultimate goal of becoming a chartered accountant. In the course of semi-structured, face-to-face interviews conducted for this study, students from across the four years of the professional degree programme, shared what had helped or hindered them on their journeys to and through Rhodes University, and within the Department of Accounting at this university. Focus group discussions were then held with academics from the department, where the student participants' experiences were shared. The responses of the members of the focus groups confirmed many of the student participants' experiences as did interviews with representatives from the South African Institute of Chartered Accountants (SAICA). These representatives also spoke about students' experiences at other campuses. To determine how localised the student participants' experiences were, selected individuals from a number of other Departments or Schools of Accounting at SAICA-accredited institutions in South Africa were also interviewed. SAICA representatives also discussed the 'pervasive skills' which trainee accountants are expected to acquire. The perspectives from these different groups, have provided validation of the student research participants' experiences. Critical Realism and Social Realism were used as theoretical underpinnings while Social Realism, Bernstein's Pedagogic Device, Legitimation Code Theory and New Literacies Theory were used as explanatory theories. Using these theories, the participants' experiences were analysed and could be understood in a different way. This dissertation reveals how this unequal privileging of individuals as a result of the existing structures is perpetuated at university level. It is the poorer students from under-resourced schools who generally struggle with the language and the practices and ways of being required for success at university. Student participants' experiences of constraint and enablement arose primarily in the areas of the finances required for tuition and living expenses while at university; having English as a language of learning; and difficulties experienced with taking advantage of the learning opportunities within the department. Research participants also spoke about their experiences of transformation in terms of both student protests, and a mentoring programme which assisted them in gaining access to the practises and ways of being required for the discipline. In so doing they were inducted into the discipline's community of practice. This dissertation has assisted in providing an understanding of what has helped and what has hindered students at Rhodes University, on their journeys towards obtaining the Postgraduate Diploma in Accounting qualification. It has also provided insight into the mechanisms which lie behind these experiences. This study will provide practitioners and policy-makers with the opportunity to be better informed about students' struggles, to contemplate their interactions with students and to identify, remove or reduce unnecessarily burdensome hurdles. Equally and perhaps more importantly, this study and the work which emerges as a result of this research, will provide students with tools to assist them in their academic journeys, to manage essential hurdles, and to eliminate or avoid unnecessary hurdles.
Keywords: Rhodes University -- Students; Accounting -- Study and teaching (Higher) -- South Africa; Education, Higher -- South Africa; Education, Higher -- Social aspects -- South Africa; Education, Higher -- Finance -- South Africa; Higher education and state -- South Africa